Tripling energy storage density through order-disorder transition induced polar nanoregions in PbZrO₃ thin films by ion implantation - Luo, Yongjian (2023)
Dielectric capacitors are widely used in pulsed power electronic devices due to their ultrahigh power densities and extremely fast charge/discharge speed. To achieve enhanced energy storage density, maximum polarization (Pmax) and breakdown strength (Eb) need to be improved simultaneously. However, these two key parameters are inversely correlated. In this study, order-disorder transition induced polar nanoregions have been achieved in PbZrO3 thin films by making use of the low-energy ion implantation, enabling us to overcome the trade-off between high polarizability and breakdown strength, which leads to the tripling of the energy storage density from 20.5 to 62.3 J/cm3 as well as the great enhancement of breakdown strength. This approach could be extended to other dielectric oxides to improve the energy storage performance, providing a new pathway for tailoring the oxide functionalities.